2017
DOI: 10.1590/1807-2577.06117
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for oral cancer in Brazil

Abstract: ResumoIntrodução: A incidência de câncer de lábio, cavidade bucal e orofaringe no Brasil é uma das maiores do mundo. Objetivo: Este estudo teve como objetivo identificar preditores para o câncer bucal no Brasil entre 2010 e 2013. Método: Mediante um estudo de série temporal em que foram avaliados 14.959 diagnósticos primários de câncer de cabeça e pescoço. As variáveis de interesse foram: gênero, idade, raça, nível de escolaridade, histórico familiar de câncer, consumo de álcool, tabagismo e diagnóstico anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
0
0
3
Order By: Relevance
“…Firstly, the study cohort’s epidemiological characteristics were consistent with those previously reported in other studies ( Wong et al, 2011 ; Rettig and D’Souza, 2015 ; Ribeiro et al, 2017 ; Johnson et al, 2020 ): the majority were male who were white, over 50 years old on average, had sustained exposure to tobacco or alcohol, and were diagnosed with locally advanced disease. Among other factors, one possible reason for the disparity in incidence rates between genders is the more frequent smoking and/or alcohol consumption among male, both of which are known to increase the risk of developing HNSCC ( Ribeiro et al, 2017 ; Chow, 2020 ). As for the late diagnosis, delay or difficulty in accessing specialized services and the devaluation of symptoms are possible causes of this observation.…”
Section: Discussionsupporting
confidence: 80%
“…Firstly, the study cohort’s epidemiological characteristics were consistent with those previously reported in other studies ( Wong et al, 2011 ; Rettig and D’Souza, 2015 ; Ribeiro et al, 2017 ; Johnson et al, 2020 ): the majority were male who were white, over 50 years old on average, had sustained exposure to tobacco or alcohol, and were diagnosed with locally advanced disease. Among other factors, one possible reason for the disparity in incidence rates between genders is the more frequent smoking and/or alcohol consumption among male, both of which are known to increase the risk of developing HNSCC ( Ribeiro et al, 2017 ; Chow, 2020 ). As for the late diagnosis, delay or difficulty in accessing specialized services and the devaluation of symptoms are possible causes of this observation.…”
Section: Discussionsupporting
confidence: 80%
“…O câncer é um grave problema de saúde mundial, é um conjunto de mais de 100 doenças que tem crescimento desordenado de células, podendo invadir tecidos e órgãos. É uma doença multifatorial onde a maior prevalência é relacionada com fatores ambientais, principalmente ao estilo de vida dos indivíduos, sendo os fatores externos substâncias químicas, radiação e vírus, já os fatores internos abrangem hormônios, condições imunológicas e mutações genéticas (causada por alterações nos genes que controlam o modo como as células do corpo humano funcionam, principalmente durante o crescimento e divisão celular), que pode iniciar em praticamente qualquer lugar do corpo humano (INCA, 2021;Ribeiro et al, 2017;SEER, 2021).…”
Section: Introductionunclassified
“…Média e mediana do tempo de espera (dias) para agendamento de consulta para a especialidade "Oncologia Ambulatório de 1ª vez-Cirurgia de Cabeça e Pescoço". Estado do RJ, 20015-2018.DISCUSSÃOO perfil etário dos usuários é consoante com o apresentado na literatura para o Brasil20 , como predomínio de usuários com idade em torno de 60 anos. Como o SER-RJ não transfere as variáveis sexo e cor/raça, de forma automática para o banco de dados, essas informações não puderam ser analisadas.…”
unclassified